EFFECT OF RECKLESSLY DISPOSED SILVER NANOPARTICLES FROM LABORATORY ON VIGNA RADIATA, BRASSICA JUNCEA, RHIZOSPHERE FLORA AND DROSOPHILA MELANOGASTER - AKHILESH BABU G.; POOJA SHRIVASTAVA; PRIYANKA SRIVASTAVA; RAMABALLABHA SAHU (International Journal of Pharma and Bio Sciences, 2013)
Present work aims to examine the effect of chemically sythesized silver nanoparticles on Vigna radiata, Brassica juncea, their rhizobacteria and Drosophila melanogaster. Silver nanoparticles were synthesized by reducing silver nitrate with sodium borohydrate in the presence of sodium citrate. UV-Vis Spectroscopy, XRD and SEM confirmed the formation of spherical silver nanoparticles in the range of 16±4 nm. The germination potential of seeds was reduced to as low as 11.07% and 27.74% when V. radiata and B. juncea were treated nanoparticle solution. Length of roots, shoots and leaf number was reduced in treated plants. Confirming the antimicrobial activity of silver, significant reduction (p<0.05) was observed in rhizosphere bacteria. In culture independent Diphenylamine assay, treated soil samples reported only 3.84 µg as compared to 8.46 µg DNA of control. Drosophila melanogaster showed marked dose- and duration-dependent decline in treated adult flies, larva and pupa. Also, malondialdehyde, the end product of lipid peroxidation and catalase activity was higher in treated flies.